Investigation on the effect of atomic defects on the breaking behaviors of gold nanowires - Wang, Fenying (2013)
The mechanical properties and breaking behaviors of the [100]-oriented single-crystal gold nanowires containing a set of defect ratios have been studied at different temperatures using molecular dynamics simulations. The size of the nanowire is 10a × 10a × 30a (a stands for lattice constant, 0.408 nm for gold). The mechanical strengths of the nanowires decrease with the increasing temperature. However, the defects that enhance the local thermal energy have improved the nanowire mechanical strength under a wide range of temperature. Comparing to the single-crystal nanowire, the existence of the atomic defects extends the elastic deformation showing a larger yield strain. By summarizing 300 samples at each temperature, the statistical breaking position distribution shows that the nanowire breaking behavior is sensitive to the atomic defects when the defect ratio is 5 % at 100 K, whereas the ratio is 1 % when temperatures are 300 and 500 K.